Nucleophilic ring-opening of benzoxazinones by dbu: some observations - Baravkar, Sachin B.; Roy, Arup; Gawade, Rupesh L.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Synthetic Communications, 2014)
This communication demonstrates the formation of an unusual nucleophilic ring opening of benzoxazinones by 1,8-diazabicycloundec-7-ene (DBU). This observation contradicts the intrinsic feature of a hindered nonnucleophilic base like DBU. Confirmation of the product was achieved via single-crystal X-ray diffraction studies.
Keywords: Benzoxazinones; caprolactam; DBU; HATU